Key hepatic signatures of human and mouse nonalcoholic steatohepatitis: A transcriptome–proteome data meta-analysis - Pyo, Jeong Joo; Choi, Yongsoo (Frontiers in Endocrinology, 2022)
Background Despite the global prevalence of nonalcoholic fatty liver disease (NAFLD), its pathophysiology remains unclear. In this study, we established highly confident nonalcoholic steatohepatitis (NASH) gene signatures and evaluated the pathological mechanisms underlying NASH through a systematic meta-analysis of transcriptome and proteome datasets obtained from NASH patients and mouse models. Methods We analyzed NASH transcriptome datasets from 539 patients and 99 mice. A whole-liver tissue proteome dataset was used to confirm the protein level dysregulation of NASH signatures significant in both humans and mice. Results In total, 254 human and 1,917 mouse NASH gene signatures were established. Up-regulated genes of 254 human signatures were associated with inflammation, steatosis, apoptosis, and extracellular matrix organization, whereas down-regulated genes were associated with response to metal ions and lipid and amino acid metabolism. When different mouse models were compared against humans, models with high fat and high fructose diet most closely resembled the genetic features of human NAFLD. Cross-species analysis revealed 66 genes that were concordantly dysregulated between human and mouse NASH. Among these, 14 genes were further validated to be dysregulated at the protein level. The resulting 14 genes included some of the well-established NASH associated genes and a promising NASH drug target. Functional enrichment analysis revealed that dysregulation of amino acid metabolism was the most significant hepatic perturbation in both human and mouse NASH. Conclusions We established the most comprehensive hepatic gene signatures for NASH in humans and mice to date. To the best of our knowledge, this is the first study to collectively analyze the common signatures between human and mouse NASH on a transcriptome–proteome scale.